Sistem Informasi Pendataan Barang Visual Berbasis WEB (Studi Kasus: PT Akur Pratama) - Sopian, Asep (TIN: Terapan Informatika Nusantara, 2020)
Web-based visual goods data collection information system. PT Akur Pratama has distributors spread across several areas such as Jakarta, Tegal, Slawi, Magelang, Bogor and Bekasi, Engaged in the trade sector headquartered in the Bandung area which has many branches in several other big cities. PT Akur Pratama has problems in data collection of goods and stock of goods, until now transaction records are still carried out manually and are inefficient and require a long time to complete the work. This resulted in the creative division at PT. Akur Pratama has difficulty getting information on items to be progressed for a theme. For this reason, more detailed information is needed such as remaining stock of goods, incoming goods, outgoing goods, placing of goods on an item shelf so as to simplify and speed up the process of finding these items. The purpose of this study is to build a data collection information system that can facilitate the creative of PT. Primary accuracy in data collection, calculating and storing data, accessing data faster and making time more efficient. The development of this system uses the waterfall method and Data Flow Diagrams (DFD) there is an analysis of running business processes, proposed business processes, analysis of functional requirements. The programming languages ​​used are PHP and MYSQL. As a database, a web-based goods data collection system that is built can manage data such as goods data, incoming goods data, outgoing goods data, supplier data and documentation data. And already have data that is centralized in one database